Successful ablation of bifocal premature ventricular complexes from both left bundle branches triggering polymorphic ventricular tachycardia in long QT syndrome 2: a case report. Issue 12 (21st December 2021) - Martinek, Martin; Kollias, Georgios; Derndorfer, Michael; Pürerfellner, Helmut
Abstract: Background: A 19-year-old woman with an established diagnosis of long QT syndrome (LQTS) 2 and underlying KCNH2-mutation was referred to our centre for recurrent polymorphic ventricular tachycardia (VT) and ventricular fibrillation (VF) refractory to medical therapy and bilateral thoracic sympathectomy. Case summary: Holter monitoring revealed a relevant premature ventricular complex (PVC) burden of two different morphologies. One PVC was originating from the left anterior fascicle, the other from the left posterior fascicle. Radiofrequency ablation resulted in complete suppression of both spontaneous PVC morphologies with a favourable clinical course over the next 2 years. Discussion: This case presents two interesting insights: firstly, the consistent bigeminal pattern of the torsade de pointes triggering PVC. These were retrieved from the device interrogation and correlated with the pattern that was seen at the time of the procedure. Secondly, PVC morphologies suggested an origin from both the left ventricular (posterior and anterior) fascicles, which have not been described so far. This was confirmed by the preceding Purkinje potentials seen at the successful ablation sites in sinus rhythm and during PVC. Ablation of triggering PVCs causing recurrent VT/VF in LQTS 2 is feasible and effective over a mid-term follow-up.